2003
DOI: 10.1557/proc-800-aa9.8
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Reactive Foils Without Igniting Them (A Femtosecond Laser Machining Approach)

Abstract: Ni/Al nanostructured multilayer foils were machined with femtosecond pulse-length laser irradiation at various fluences. Scanning electron microscopy, back-scattered electron detection, and atomic force microscopy were used to characterize the resulting laser modified regions. We show that material removal at the micron scale is possible with no ignition of a self-propagation reaction emanating from the irradiated areas, a danger minimized by the fact that the extremely short time duration of the pulse produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…However, the nanosecond-pulse ignition fluences are less than the nanosecond threshold fluence for removing Pt (~0.49 ± 0.026 J/cm 2 ; 3.06 × 10 18 eV/cm 2 ) [134]. Thus, one strategy for laser machining reactive multilayers involves femtosecond pulses [136].…”
Section: Laser Ignitionmentioning
confidence: 99%
“…However, the nanosecond-pulse ignition fluences are less than the nanosecond threshold fluence for removing Pt (~0.49 ± 0.026 J/cm 2 ; 3.06 × 10 18 eV/cm 2 ) [134]. Thus, one strategy for laser machining reactive multilayers involves femtosecond pulses [136].…”
Section: Laser Ignitionmentioning
confidence: 99%
“…Although the ablation thresholds for Ni, Al, and their intermetallic compounds [33][34][35] are within similar orders of magnitude, previous research [30] suggests layer-by-layer ablation of the individual Ni and Al double layers. Applying this consideration on the conducted single pass processing of Ni/Al at either 1 kHz or 5 kHz, a deviation in the development of the advancing cut edge morphology can be suggested.…”
Section: Formation Of the Oxide Layer And Debris Depositionmentioning
confidence: 70%
“…This further limits the time frame for quantitative thermal diffusion [31]. Previous studies more focused on ignition thresholds have shown that is possible to cut through Co/Al multilayers [16] and remove a few layers of Ni/Al [30] without ignition of self-propagating reactions at higher fluences than the ones used in this work. According to the manufacturer of the Ni/Al multilayers used in this study, cutting using nanosecond (ns) lasers is also possible at high pulse rates (i.e., low pulse energy).…”
Section: Laser Machining Of Ni/al Reactive Multilayer Foilsmentioning
confidence: 95%
See 1 more Smart Citation